META-ANALYSIS OF THE EFFECTIVENESS OF PROBLEM-BASED LEARNING (PBL) MODELS AT THE MIDDLE SCHOOL LEVEL - Adinda Fara Aulia; Azizah Miftakhul Rohmah; Setia Rahmawan (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2024)
This research investigates the effectiveness of the Problem-Based Learning (PBL) learning model in improving student learning outcomes at the junior high school level using two cycles of Classroom Action Research (PTK). The PBL learning model can attract students' attention so that they become more active and collaborative. Applying the PBL model can improve problem-solving abilities so that students can think critically. However, there are still challenges in implementing PBL, such as limited resources, the time needed to prepare material, and the teacher's ability to manage dynamic classes. The method used is meta-analysis which is reviewed from a literature review. A literature review is analyzing information from someone's published research. The research began by searching for data in the form of descriptive analysis. The results of the study of the PBL model with two cycles can improve student learning outcomes from the lowest, namely 3.07% to the highest, 42.8%. The results of data analysis in Table 1 mean the first cycle score is 71.78, while the average second cycle score is 85.66. The average score shows a significant change, proving that the use of the Problem-Based Learning model is an effective solution for teachers to improve student learning outcomes at the junior high school level.